Digital Financial Inclusion, MSMEs, and Inclusive Growth: Empirical Evidence from Districts/Cities in Indonesia - Abdullah, Maman (Cattleya Darmaya Fortuna, 2025)
The transformation of digital financial services—through e-wallets,QRIS, branchless banking, and fintech—is seen as capable ofreducing transaction costs and expanding access to financing forMSMEs. This study assesses the extent to which digital financialinclusion (DFI) drives inclusive growth at the district/city level inIndonesia. We construct a composite DFI index that emphasizesthree dimensions—access, usage, and quality—and link it toinclusive growth indicators: real GRDP growth in labor-intensiveMSME sectors, MSME employment, and inequality proxies.Methodologically, the study adopts a panel data design with twowayfixed effects, enriching identification through a spatial panelmodel (to capture spillovers between regions) and a quasiexperimentalstrategy (staggered Difference-in-Differences) thatexploits variations in digital transaction adoption/intensificationacross time and region. Potential endogeneity is addressed usinginstruments based on digital infrastructure availability andtopography. The results show that increased DFI is positively andeconomically meaningfully associated with the Inclusive GrowthIndex (IGI), through reduced payment friction, market expansion,and improved MSME financing eligibility. Heterogeneity findingsindicate greater marginal benefits in regions with higher digitalreadiness, while evidence of spatial spillovers suggests spillovereffects to neighboring regions. Policy implications emphasizeaccelerating infrastructure and ecosystem (agent/merchant)density, reducing microtransaction costs, strengthening digitalfinancial literacy, and integrating transaction data for inclusivefinancing with consumer protection. The novelty of this study liesin the construction of a district/city-level DFI index that focuses onuse and quality, a truly inclusive growth measurement, and acombination of spatial identification and quasi-experimentalmethods that strengthen causal inference.